Avaliação ecodinâmica das unidades de paisagem da sub-bacia hidrográfica do rio do Sal - Santos Neto, José Arnaldo dos (2020)
The new technologies have enabled modern society to believe they have the knowledge and tools necessary to control the dynamics of nature and expand the use of natural resources. Among the most explored, water stands out as a water resource. The area of this research encompasses the sub-basin of the Sal River, the main tributary of the right bank, of the Sergipe River, a natural boundary between Aracaju and Nossa Senhora do Socorro. This study aims to evaluate the state of the landscape units of the Sal River sub-basin, according to the principles of Ecodynamics (TRICART, 1977). Due to the sub-function it has two areas with different characteristics of use and occupation, a rural area and an urban area, the original ecodynamic means were adapted to this reality. The studies were supported by the systemic approach, in the landscape category, and the geosystemic model (BERTRAND, 2004) applied to the compartmentalization of landscape units, based on geomorphology. Methodological procedures adopted included: bibliographic research, survey of the documentary and cartographic collection, analysis of socioeconomic data taken from state and federal agencies, interpretation of satellite images, preparation of thematic maps and fieldwork. Thematic maps were made using geoprocessing software. The results obtained indicate that the landscape of the sub-basin is composed by two Geosystems and four Geofacies: - Coastal Geosystem formed by Geofacies Surface dissected in hills, tabular interfluvia and hills, and Geofacies Strand dissected in smooth convex hills and spikes along; - Coastal Plain Geosystem integrated by Fluviomarine Plain Geofacies and Marine Terraces - Pleistocene and Holocene Geofacies. Each landscape unit is in a certain evolutionary stage. In general, the Relatively Unstable Media in the sub-basin and the Relatively Unstable Urban-ecodynamic Media in the Urban Area predominate in the subbasin. The insertion of human action in natural dynamics translates into changes in the landscape and environmental problems, sometimes of control or irreversible. The study carried out in the Rio do Sal hydrographic sub-basin makes evident the importance of geoenvironmental analysis and assessment of the state of the landscape, as a way of making auxiliary decisions for territorial management, enabling an improvement in the quality of life of the population and conservation of natural resources, which they can use consciously.